CREATIVE CITY AS A FACTOR OF DIGITAL SOCIETY DEVELOPMENT - Voronkova, V.; Nikitenko, V. (Municipal economy of cities. Series: «Economy science», 2022)
The article summarizes the study of the phenomenon of the creative city as a factor of digital society development in that it aims to solve the problems of the city as a complex social, economic, cultural phenomenon of XXI century digital era. The solution of the problems of the "creative city", which should be implemented in its practice, innovation, creativity, intelligence, which are fundamental for the use of digital technologies, is revealed. They are the condition for the implementation of a set of innovations in the digital society. The aim of the article is to conceptualize the creative city as a factor of the development of a digital society that develops in the context of such categories as "smart city", innovation, creativity, cultural planning. The research methodology is analyzed, which includes Agile-methodology as a theoretical basis of the digital society, which allows to reconsider radically the mission, functions, legitimacy, tools of activity in the creative city. The combination of synergetic, systemic and axiological methods and approaches allows to explain the peculiarities of the development of the creative city in order to increase the efficiency of digitalization of society. The social and axiological method revealed the values of the digital society, which is based on the cultural planning of the city, the cultural functions of man and the state. At the heart of the cultural sphere management of the creative city - the development of cultural organizations, which involves the use of cultural knowledge, insider processes, the use of cultural potential of the individual, which can change the development of the organization and the city. The combination of creativity and innovation, which contribute to the transformation of a creative city into a smart city based on digitalization, is revealed. The directions of development of digital technologies of the creative and smart city are considered and the management of the creative city in the context of development of cultural resources is analyzed. Therefore, the functions of digitalization should be developed to constantly support this creative ecology of the city. The opportunity to use effectively the resources of the city and its cultural resources using digital technologies will contribute to the formation of a digital city. The scientific novelty of the study in the analysis of a new problem, which has not yet been analyzed in the domestic social and philosophical literature and is of great practical importance for modern Ukrainian society. The practical significance of the theme of the creative city as a factor in the development of digital society is that it is studied in the context of cultural management.